Penerapan Macromedia Flash dalam Meningkatkan Kreativitas, Hasil Belajar, dan Efektivitas Pembelajaran Siswa Kelas XII di SMK Negeri 1 Kaliorang - Rudi Hartono; Susilo Susilo; Yusak Hudiyono (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
Indonesian subjects have different levels of difficulty so there needs to be variations in learning, so students do not get bored. To implement the objectives of the Indonesian language subject, Indonesian language learning in the 2013 curriculum is presented using a text-based approach. In addition, the use of instructional media in the learning process will reduce student dependence on teachers. The implementation of learning media aims to (1) how is the application of learning media macromedia flash in improving student learning creativity in Indonesian language lessons; (2) how is the application of macromedia flash learning media in improving student learning outcomes in Indonesian language lessons; and (3) how is the effectiveness of macromedia flash learning media in increasing creativity and student learning outcomes in Indonesian language lessons. The subjects of this study were students of class XII at SMK Negeri 1 Kaliorang. This type of research is included in the Classroom Action Research (CAR) whose steps are as follows (1) planning, (2) implementation; (3) observation, and (4) reflection. Retrieval of research data through observation, written tests, and questionnaires with research instruments in the form of (1) observation sheets, (2) test questions, and (3) questionnaire sheet. After conducting research Application of audio-visual learning media can improve student learning outcomes in class XII SMK Negeri 1 Kaliorang, the learning outcomes are evidenced by an increase in test results at the end of each cycle. Improved learning outcomes seen from mastery learning in the first cycle that is 53.33% and 83.33% in the second cycle.